Comparative efficacy of inhaled ciclesonide, budesonide, and fluticasone in mild to moderately persistent bronchial asthma - Maiti, Tamoghna; Naser, Syed Mohammed; Panda, Amrita; Mandal, Sekhar; Mandal, Sonai; Gangopadhyay, Tanmoy; Banu, Parvin (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Bronchodilators and glucocorticoids have been proven to be very effective and safe in asthma treatment, which recommend the use of steroids and β2-agonist (long or short acting) as the first line of treatment in of asthma. This study was aimed to compare the efficacy of three different inhaled corticosteroids ciclesonide, budesonide, and fluticasone in bronchial asthma. Methods: A total of 30 patients with mild to moderately persistent bronchial asthma was selected as per the NAEPP classification in the expert panel report (EPR) update 2002, NHLBL USA 2003. They were randomly divided into 3 groups of 10 patients each, and they were given 3 different steroid inhalers (ciclesonide or budesonide or fluticasone). Baseline and post-therapy spirometry were performed on day 1 and after 2 months and 6 months of treatment. Data were analyzed using SPSS software. Results: It was observed that most of the cases (43.3%) were between 26 and 35 years of age with female preponderance (56.6%). Significant symptomatic improvement was observed in all 3 groups. The percentage of improvement in mean peak expiratory flow rate was 17%, 18%, and 18% in ciclesonide, budesonide, and fluticasone group, respectively. The percentage improvement of forced expiratory volume in 1 second (FEV1)/forced vital capacity after bronchodilatation was 18%, 18%, and 19% in ciclesonide, budesonide, and fluticasone group, respectively. The improvement in mean FEV1% predicted was 20%, 19%, and 21% in three groups, respectively. Conclusion: Steroid therapy along with β2-agonists showed a significant improvement in symptoms. There was no difference among the three different types of steroids.